Analisis Pengaruh Profitabilitas dan Likuiditas Terhadap Return Saham PT Indofood CBP Sukses Makmur Tbk Tahun 2016-2023 - Dewi, Maylisa Atika Sasaki; Siska, Elmira (Pusat Riset dan Inovasi Nasional, 2024)
The study aims to determine the impact of profitability measured by Return On Asset (ROA) and liquidity measufied by Current Ratio (CR), partially and simultaneously on the share return of PT Indofood Sukses Makmur Tbk company listed on the Indonesian Stock Exchange (BEI) in 2016-2023. The search was carried out in April-May 2024. Data collection techniques use documentation studies by analyzing financial statements. Data analysis techniques include classical assumption tests, double linear regression, t tests and F tests. The results show that the data used does not have econometric problems. Return On Asset (ROA) has a passively negative and significant impact on the share return (t count 3,874 > t table 2,4227). Current Ratio (CR) is partially positive and significant (t t count 4,933 > t Table 2,4227. Simultaneously, ROA and CR have a positive and meaningful effect on the stock return (F count > F table 12,906 > 3,328). Keywords: Return On Asset (ROA), Current Ratio (CR), Stock Return.